Circulating microRNAs as biomarkers for metabolic disease. Issue 5 (October 2016) - Párrizas, Marcelina; Novials, Anna
Abstract : Incidence of diabetes and other metabolic disorders is increasing worldwide, with almost half the cases remaining undiagnosed. This is cause for concern as poor management of glucose or lipid levels causes tissue damage that may result in micro- or macrovascular complications. Current methods of diagnosing metabolic disorders do not provide any clues on disease aetiology or their posterior evolution and incidence of complications, which are the main cause of disease-associated morbidity. Circulating microRNAs found in blood change with the physiological condition of the organism and may help to: (1) identify people at risk of developing metabolic disease, (2) diagnose diabetes or other metabolic disorders on the basis of their aetiology, (3) predict the development of complications, and (4) monitor response to treatment. Results published to date show promise in this direction but technical issues must still be honed in order to warrant their application in the clinical practice.